Baby's day out - Hughes, John; Johnson, Patrick Read; Ryan, William; Vane, Richard (John Hughes Production, 1995)
The story of a baby who traveled out of town alone for the day. Frantically hunted by his mother and turned into a celebrity by the media, Baby Bink stays one step ahead of a trio of con artists eager to collect the reward money being offered by his parents - cool, calm, collected and totally unaware of the havoc he wreaks. Baby Bink's day-trip is a hilarious mix of comedy and groundbreaking special effects.